Integrating technology and organization for manufacturing sector performance: evidence from Finland - Heilala, Janne (fi=Turun yliopisto|en=University of Turku|, 2024)
This dissertation investigates the complex factors shaping the future of manufacturing, focusing on innovation, competitiveness, and employment trends within the European context. Leveraging the extensive 2022 European Manufacturing Survey dataset, it models relationships between critical technological and organizational variables impacting manufacturing resilience using cross-lagged panel path analysis. Against the 2019–2021 economic and environmental backdrop, the research examines manufacturers’ integral survival strategies derived from challenges faced. Factors like business innovation models, organizational concepts, key technologies, and relocation approaches are assessed for performance. The study reveals competitive standards: automation, robotics, additive manufacturing, accessbased business models, maintenance services, and production organization. These discoveries have profound implications for enabling the transition to next-generation sustainable manufacturing through technology integration frameworks. The research marks the need for investments in cross-sectoral research coordination. As climate change intensifies, reimagining manufacturing is critical. While acknowledging limitations like sample size and scope, the dissertation offers a detailed understanding of the manufacturing system’s components and the relationships of success, forward strategies, and human-technology-environment interlinkages. This multidimensional perspective provides insight to catalyze the creation of integrated manufacturing ecosystems worldwide.